Development of a model for blended learning in traditional universities in Palestine / Ghassan O A Shahin - Ghassan, O A Shahin (2012)
Many institutions of higher education are incorporating e-learning into their curriculum. Several factors though, need to be taken into consideration when implementing e-learning. One way to help in overcoming barriers facing efforts of higher education in Palestine to move towards implementing e-learning is to adopt blended learning approach. The research is aimed at developing a model of blended learning that can be applied in traditional universities in Palestine. Information was first obtained through a questionnaire distributed among faculty members in Palestine to determine the problems and needs of implementing e-learning in higher education. Factors for blended learning were determined based on the literature and the input from the data. A blended learning model was then developed, consisting of blends of face-to-face and Internet settings, synchronous and asynchronous communications, learning theories, instructional strategies, delivery methods and types of contents, in addition to learning style test component. It is based on factors and quality criteria related to blended learning. Evaluation of the model design was carried out among faculty members in Palestinian universities through a questionnaire. The Cronbach‘s alpha value for all items was 0.963, and the mean for all items was 4.16, with 38 items scoring a Mean of >=4.0, and with minimum individual question mean of 3.67 and maximum of 4.55. This suggests that the model is acceptable. Then, software was developed and implemented to proof the applicability of the model. The model was then tested in one university in Palestine. Volunteer lecturers tested the model for 2 weeks, as part of their taught courses, where they gave feedback on the model execution. Students were also asked to complete a questionnaire regarding their experience with the model. The model was tested for learner satisfaction, motivation, communications between learners and lecturer, and cost. The Cronbach‘s Alpha for all items was 0.982, and 0.984 for Likert- iv type items, with 48 valid cases out of 57. The mean was 4.768 indicating the model was evaluated considerably good. Exploratory factor analysis was conducted and six factors - motivation, satisfaction, communication and interaction, time and cost saving, ease of use, and support and needs - were extracted. The results showed good level of satisfaction, motivation and improved communications among participating students, while time and cost factor scored the highest mean of 4.968 which indicate that students were concerned about it, and perceived the model as decreasing cost and providing flexible time. Students and lecturers indicated that they prefer this model over traditional one. The main contribution of this research is the development of a blended learning model for traditional universities based on factors such as instructor characteristics, learner characteristics, infrastructure, cost, pedagogy, time, political, legal, language, delivery mode and instructional technology factors, incorporating learning style test results and using them as guide for both learners and lecturers in the learning process. Another contribution is a guidelines document for traditional universities to implement blended learning. In addition, the study contributed in filling the gap of scarce literature about e-learning in Palestine.